Prywatne ubezpieczenia zdrowotne w Polsce - Prędkiewicz, Paweł (Private Health Insurance in Poland, 2006)
The appearance of international investors in polish economy and growth of wealth were the cause of growing requirements of patients. With worse and worse situation in public health care, it was an impulse for development of private medical centers and alternative methods of payment. One of these methods is the system of private health insurance. Although they aren't a main source of polish health financing, their role will become more significant in next years.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1103, s. 251-261